Pulsed laser-driven molecular self-assembly of cephalexin: aggregation-induced fluorescence and its utility as a mercury ion sensor - Singh, Pradeep Kumar; Prabhune, Asmita; Ogale, Satishchandra (Photochemistry and Photobiology, 2015)
A fluorescent self-assembly of cephalexin is obtained by pulsed laser irradiation process. An intense fluorescence emission is found in the self-assembled form due to occurrence of a typical aggregation-induced emission in cephalexin molecules. It is observed that fluorescence quenching of the self-assembled fluorescent nanostructures occurs in the presence of extremely low Hg++ ions concentrations (10(-7) M) as compared to other heavy metal ions e.g. Ferrous (Fe++), Manganese (Mn++), Magnesium (Mg++), Cobalt (Co++), Nickel (Ni++) and Zinc (Zn++) at the same concentrations.